ANALYSIS OF IMPLEMENTATION STANDAR AKUNTANSI KEUANGAN TANPA AKUNTABILITAS PUBLIK (SAK ETAP) ON THE MICRO SMALL AND MEDIUM ENTERPRISES (MSMES) SUTOMO JAYA BUILDING SHOP - B41112132, Jimi (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
ABSTRACT The financial report is a tool analyzing the financial performance of companies that can provide information about the financial position, performance and cash flow,so it can serve as a basis for decision making by management. Accounting Standards Entities Without Public Accountability (SAK ETAP) is an accounting standard set for ease of preparation and presentation of financial statements for MSMEs. The information presented in the financial statements may provide ease in lending assistance to the creditor institutions to MSMEs. This study was designed to produce a simple financial statements format based on SAK ETAP for MSMEs. The object of this study is MSMEs Sutomo Jaya Building shop located in Pontianak engaged in the sale of building material. The purpose of this study was to determine the suitability of the financial statements which is owned by MSMEs with the financial statements SAK ETAP. This study is a qualitative research and data collection techniques used is through observation, interviews,and literature study. Results of research conducted concluded that the financial statements of MSMEs Sutomo Jaya Building shop not apply SAK ETAP. This is because MSMEs only provide a simple income statement in the financial statements. Factors that cause SAK ETAP has not been applied in preparing the financial statements is the lack of understanding of accounting from the owners and employees as well as the lack of participation of the government to conduct socialization and training to MSMEs on SAK ETAP. Keywords: MSMEs Sutomo Jaya Building shop, SAK ETAP, Financial Statements